Risk and risk management in Hungarian sheep production - Nábrádi , András; Madai, Hajnalka (Applied Studies in Agribusiness and Commerce, 2007)
The aim of this paper is to give an overview of the risk attitudes of Hungarian sheep producers regarding the changes they have had to go through since the political changes of 1989–1990. Moreover, the objective of this study is to strengthen the empirical basis for risk analysis by identifying the importance of farmers’ risk attitudes. The results of a nationwide survey of over 500 sheep farmers presented a framework of risk attitudes, risk sources and applied risk management techniques of livestock producers.